Equitable Educational Infrastructure via Policy Execution and Stakeholder Involvement in Educational Institutions - Hasyim, Nasaruddin (ASHA Publishing, 2025)
Fair access to educational infrastructure continues to be a significant issue in numerous areas, especially in disadvantaged and under-resourced groups. This qualitative study examines the impact of education policy on the creation and allocation of school infrastructure, emphasizing the viewpoints of essential stakeholders such as educators, policymakers, and community leaders. The study reveals that although equitable rules are in place, their efficacy is significantly contingent upon context-specific implementation, stakeholder engagement, and local leadership. Participants identified obstacles that included bureaucratic impediments, insufficient consultation procedures, and the necessity for more inclusive planning. The results indicate that proactive community involvement and tailored policy frameworks are crucial for mitigating inequalities in infrastructure development. The report underscores the imperative for ongoing professional development for educators and administrators to effectively navigate policy contexts. This study contextualizes policy within the experiences of educational stakeholders, providing ideas for enhancing infrastructural equity and contributing to the dialogue on sustainable educational reform. The conclusions promote a more cohesive and inclusive methodology for policy formulation and implementation, harmonizing national strategies with local requirements.